Top answers

Maths
A Level

The function f (x) is defined by f (x) = (1-x)/(1+x), x not equal to -1. Show that f(f (x)) = x. Hence write down f ^-1 (x).

f(f (x) )= f( (1-x)/(1+x) ) = (1-(1-x)/(1+x))/(1+(1-x)/(1+x))where you replace x by (1-x)/(1+x). Multiply the top and bottom of the fraction by (1+x) to get ((1+x)-(1-x))/((1+x)+(1-x)) which simplifies t...

Answered by Sarah P. Maths tutor
9781 Views

What is the normal distribution and how do I use it?

The normal distribution is a distribution we can use when we know the mean and the standard deviation of a population, to work out probabilities that a certain even will occur.
The main properties of...

Answered by Chantelle C. Maths tutor
2933 Views

Integrate x/((1-x^2)^0.5) with respect to x

x = sin(u), dx/du = cos(u), dx = cos(u) * du,[x/(1-x^2)^0.5)] * dx = [sin(u)/((1-(sin(u)^2))^0.5] * cos(u) * du = [sin(u)/(cos(u)^2)^0.5] * cos(u) * du = sin(u) * duIntegral of sin(u) * du = -cos(u) = -(...

Answered by Andrew P. Maths tutor
3746 Views

Express 5/[(x-1)(3x+2)] as partial fractions.

5 = a(3x+2) + b(x-1), x = 1, 5 = a(3+2) +b (1-1), 5 = a(5) + b(0), 5 = 5a, a = 1, x = -2/3, 5 = a(-2+2) + b(-(2/3)-1), 5 = a(0) + b(-5/3), 5 = -5b/3, b = -3, Therefore: 5/[(x-1)(3x+2)] = 1/(x-1) -3/(3...

Answered by Andrew P. Maths tutor
6945 Views

Differentiate sin(x)cos(x) with respect to x?

You will have to use the Product Rule. The Product rule: when y=f(x)g(x), then dy/dx=f'(x)g(x)+f(x)g'(x). In this example, f(x)=sin(x) and g(x)=cos(x). Hence f'(x)=cos(x) and g'(x)=-sin(x). Using these an...

Answered by Matthew M. Maths tutor
4104 Views

We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences